2019
DOI: 10.1097/nne.0000000000000549
|View full text |Cite
|
Sign up to set email alerts
|

Canine Outreach Promoting Engagement

Abstract: Animal-assisted activities (AAAs) show promise in providing emotional and social benefits to older adults and may be used as a tool to promote therapeutic communication between students and cognitively impaired older adults. The purpose was to develop a program incorporating AAAs to enhance social engagement of cognitively impaired older adults in a community respite program and in turn enhance student comfort when caring for this vulnerable population. The Dementia Attitudes Scale, a validated tool, was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Finally, it is critical to target students who may not have ready access to their dogs as walking partners. A recent survey that evaluated the effects of animal assisted therapy (AAT) programs on nursing students and the older patients discovered that there is a large percentage of students who own dogs, but do not have access to regular interaction with their dogs, as ~56% of students said they left their dog in their hometown with their parents (Yordy, Pope, & Wang, 2018). This means there is likely an unrecognized loss of emotional support for these students who are separated from canine companions while at school, which in turn may be affecting their mental and emotional health.…”
Section: Recommendationsmentioning
confidence: 99%
“…Finally, it is critical to target students who may not have ready access to their dogs as walking partners. A recent survey that evaluated the effects of animal assisted therapy (AAT) programs on nursing students and the older patients discovered that there is a large percentage of students who own dogs, but do not have access to regular interaction with their dogs, as ~56% of students said they left their dog in their hometown with their parents (Yordy, Pope, & Wang, 2018). This means there is likely an unrecognized loss of emotional support for these students who are separated from canine companions while at school, which in turn may be affecting their mental and emotional health.…”
Section: Recommendationsmentioning
confidence: 99%
“…Within this model, step 4 focuses on communication and consultation between the disciplines. Evidence suggests an increase in communication between 2 or more parties in the presence of canines; 9 therefore, the use of canines within the school setting could meet step 4 of the model. As AAT shifts to additional settings, the human-animal bond could be a promising intervention to bring 2 disciplines, who often work in silos, together in a collaborative relationship to benefit students with complex chronic health conditions 3 and to tackle the rise of traumatic events occurring in school-aged children 4…”
mentioning
confidence: 99%
“…There are also secondary benefits of animal interaction including enhanced communication. Research has shown evidence that canines often are the facilitator through which 2 parties engage in communication 9 . One approach will be teaching school counselors and school nurses how to develop an AAT program or use their existing program to engage each discipline in more communication.…”
mentioning
confidence: 99%